Personal reflections on the COPSS Presidents’ Award (Past, Present, and Future of Statistical Science, 2014)
I received the COPSS Presidents’ Award in 1988, one year after Jeff Wu and one year before Peter Hall. I was the eighth recipient.I had just moved to Texas A&M in fall 1987, and did not know that Cliff Spiegelman, also still at Texas A&M, had nominated me. I remember very clearly being told about this honor. I was working at home, and out of the blue I received a phone call from the head of the Presidents’ Award Committee, about a month before the Joint Statistical Meetings in New Orleans, and he asked, roughly, “are you going to the JSM in New Orleans?” I actually had not planned on it, and he told me I probably should since I had won the Presidents’ Award. I remember being very happy, and I know I took the rest of the day off and just floated around.